The influence of a three week familiarisation period on rowing mechanics at a new stretcher position - Caplan, N.; Gardner, T. (International Journal of Sports Science and Engineering, 2008)
The height of the foot plates (stretchers) in rowing have been shown, both theoretically and experimentally, to significantly influence the effectiveness of the rowing stroke. However, the extent to which increasing this height can improve rowing performance, through musculo-skeletal adaptations, is not yet known. The aims of the present investigation were to determine the influence of a three week familiarisation period on rowing performance at a raised stretcher height. Nine male rowers performed a 3.5 minute maximal intensity ergometer trial before and after familiarisation. Mean power per stroke significantly increases during the first, middle and last ten strokes of the trial, post-familiarisation. This increase in mean power per stroke was due to increases in both mean handle force and velocity. The results of the study suggested that a musculo-skeletal adaptation to this new stretcher position had occurred with familiarisation, leading to improved performance. Determination of an ideal stretcher height for maximum mechanical effectiveness was not possible here, as this would be specific to each individual rower, and must take into consideration the balance of the boat and the extra energy required to maintain balance as stretcher height is increased. However, the importance of determining this height is now clearly understood.